2009
DOI: 10.4049/jimmunol.0900509
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Cationic Protein (ECP) Is Processed during Secretion

Abstract: The eosinophil granulocyte is an inflammatory cell involved in allergic diseases such as asthma and rhinitis. Eosinophil cationic protein (ECP) is a basic and potentially cytotoxic granule protein that is released from the eosinophil upon activation. The aim was to study secretion of molecular variants of ECP from blood eosinophils with the hypothesis that the stored noncytotoxic ECP is altered into cytotoxic species upon release from the cell. Eosinophil granulocytes were purified to >95% from venous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 26 publications
2
45
0
2
Order By: Relevance
“…These ECP genotypes also show associations with the symptoms of allergy and asthma (80,81). Venge and colleagues (82) reported that the various ECP glycoforms are processed during eosinophil secretion; the modifications to secreted ECP by activated eosinophils is explained in part by differences in their degree of N-linked glycosylation, such that secreted ECP acquires the masses of the more cytotoxic, less glycosylated, isoforms, including the nonglycosylated species (82), explaining in part the structural and functional heterogeneity of ECP as reported in the literature.…”
Section: Eosinophil Cationic Proteinmentioning
confidence: 97%
“…These ECP genotypes also show associations with the symptoms of allergy and asthma (80,81). Venge and colleagues (82) reported that the various ECP glycoforms are processed during eosinophil secretion; the modifications to secreted ECP by activated eosinophils is explained in part by differences in their degree of N-linked glycosylation, such that secreted ECP acquires the masses of the more cytotoxic, less glycosylated, isoforms, including the nonglycosylated species (82), explaining in part the structural and functional heterogeneity of ECP as reported in the literature.…”
Section: Eosinophil Cationic Proteinmentioning
confidence: 97%
“…Inflammasomes are multiprotein cytoplasmic complexes that mediate the activation of inflammatory caspase-1 (Woschnagg et al, 2009). Inflammasome regulates the activation and secretion of caspase 1-regulated IL-1β and IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…Site-directed mutagenesis studies identifi ed the main critical residues exposed at the protein surface involved in membrane lysis and cytotoxicity (Carreras et al , 2003 ;Torrent et al , 2007 ;Singh and Batra , 2011 ). Additionally, complementary studies on the protein native posttranslational forms and comparison of polymorphism variants highlighted the contribution of glycosylation on the protein cytotoxic power (Trulson et al , 2007 ;Rubin et al , 2009 ;Woschnagg et al , 2009 ). In the following section, we detail the current knowledge on ECP antimicrobial properties.…”
Section: The Eosinophil Cationic Protein (Ecp) In Host Defencementioning
confidence: 99%
“…In fact, the proteolytic processing is used extensively in immunology cascade events. A local cleavage can release the active peptides in the infection area in the same manner as cecropin is released from cathelicidins expressed in neutrophils (Zanetti et al , 1995 ;Burton and Steel , 2009 ), lactoferricin is derived from the N-terminus (Krieg et al , 1998 ;Clark et al , 2003 ); Tyr33 nitration (Ulrich et al , 2008 ) Host defense against viral infections; chemotaxis for dendritic cells (Rosenberg , 2008a ) RNase 3 (tested against several Gram-negative and -positive species (Torrent et al , 2009b(Torrent et al , , 2011b Arg97/Thr (related to asthma propensity and disease-induced pathologies) (Eriksson et al, 2007a;Adu et al , 2011 ) Gly103Arg 3 potential N-glycosylation sites; 10 purifi ed variants of N-linked glycosylated forms (Eriksson et al , 2007b ); N-glycosylation processed upon secretion by activated eosinophils (Woschnagg et al , 2009 );…”
Section: Introduction: Antimicrobial Rnasesmentioning
confidence: 99%